Noninvasive Approach to Focal Cortical Dysplasias: Clinical, EEG, and Neuroimaging Features - Seifer, Gustavo (2012)
Purpose. The main purpose is to define more accurately the epileptogenic zone (EZ) with noninvasive methods in those patients with MRI diagnosis of focal cortical dysplasia (FCD) and epilepsy who are candidates of epilepsy surgery. Methods. Twenty patients were evaluated prospectively between 2007 and 2010 with comprehensive clinical evaluation, video-electroencephalography, diffusion tensor imaging (DTI), and high-resolution EEG to localize the equivalent current dipole (ECD). Key Findings. In 11 cases with white matter asymmetries in DTI the ECDs were located next to lesion on MRI with mean distance of 14.63 millimeters with topographical correlation with the EZ. Significance. We could establish a hypothesis of EZ based on Video-EEG, high-resolution EEG, ECD method, MRI, and DTI. These results are consistent with the hypothesis that the EZ in the FCD is complex and is often larger than visible lesion in MRI.